N6-methyladenosine modified LINC00901 promotes pancreatic cancer progression through IGF2BP2/MYC axis - Peng, Wan-Xin; Liu, Fei; Jiang, Jia-Hong; Yuan, Hang; Zhang, Ziqiang; Yang, Liu; Mo, Yin-Yuan (Genes & diseases, 2023)
Accumulating evidence indicates that RNA methylation at N6-methyladenosine (m6A) plays an important regulatory role in gene expression and aberrant mRNA m6A modification is often associated with a variety of cancers. However, little is known whether and how m6A-modification impacts long non-coding RNA (lncRNA) and lncRNA-mediated tumorigenesis, particularly in pancreatic ductal adenocarcinoma (PDAC). In the present study, we report that a previously uncharacterized lncRNA, LINC00901, promotes pancreatic cancer cell growth and invasion and moreover, LINC00901 is subject to m6A modification which regulates its expression. In this regard, YTHDF1 serves as a reader for the m6A modified LINC00901 and downregulates the LINC00901 level. Notably, two conserved m6A sites in LINC00901 are critical to the recognition of LINC00901 by YTHDF1. Finally, RNA sequencing (RNA-seq) and gene function analysis revealed that LINC00901 positively regulates MYC through upregulation of IGF2BP2, a known RNA binding protein that can enhance MYC mRNA stability. Together, our results suggest that there is a LINC00901-IGF2BP2-MYC axis through which LINC00901 promotes PDAC progression in an m6A dependent manner.